Deep-sea coral recording of the neodymium isotope signature of Labrador Sea intermediate water at sporadic intervals over the last two climatic cycles - Claude Hillaire-Marcel; Jenny Maccali; Evan Edinger; André Poirier (Quaternary Science Reviews, 2025)

Drivers of Coral and Sponge Community Composition and Size Structure Revealed With Cumulative Abundance Profiles - Johanne Vad; Jason Cleland; Laurence H. De Clippele; Evert de Froe; Georgios Kazanidis; Sabena Blackbird; Dick Van Oevelen; Erica Head; Igor Yashayaev; Ellen Kenchington; Bárbara de Moura Neves; Evan Edinger; et al. (Marine Ecology, 2025)
Deep‐sea corals and sponges form ecologically significant habitats that support biodiversity hotspots and contribute to important ecosystem functions such as carbon and nutrient cycling as well as benthic‐pelagic coupling. However, quantifying their contributions to ecosystem functioning requires examination not only of the fine spatial distribution of community composition but also community size structure, because larger individuals are expected to contribute more to ecosystem functions than smaller ones. Here we create novel cumulative abundance profiles (CAPs) by combining body size structure with species abundance data to identify ecological drivers of sponge and coral community composition and size structure. Data were collected from 226 drop camera images captured near Saglek Bank, on the northern Labrador shelf and upper slope in the northwest Atlantic. The density of four coral and 17 sponge morphospecies were recorded from each image. The surface area covered by coral and sponge specimens was measured (1458 measurements in total) and converted to size estimates using data from live specimens collected with a rock dredge. Cumulative abundance profiles were then constructed and combined with cluster analysis to identify distinct community assemblages. In addition, distance‐based redundancy analysis was used to identify environmental drivers influencing cluster community composition and/or size structure. Finally, organic carbon turnover was calculated for each cluster using published respiration data. Three assemblages were identified with differing composition and size structures. One of these was characterized by large coral and sponge morphospecies and individuals. The spatial distribution of this cluster was controlled by interactions between substrate type, terrain position index (TPI) and orientation of the slope (eastness). When analysing composition or size structure separately, dissolved oxygen and current speed respectively were also identified as key parameters. This finding indicates that substrate type and TPI influence the presence of coral and sponges in the study area, while dissolved oxygen may constrain which morphospecies are present and bottom currents restrict the size of individuals. As predicted, high levels of carbon turnover were driven by large sponge and coral individuals, likely maintained in part by the sponge loop in which sponges recycle dissolved organic matter into particulate organic matter. This study gives the first demonstration of how CAPs can be used to analyse spatial variation in deep‐sea benthic community composition and size structure and appropriately quantify contribution to ecosystem functions such as carbon turnover.

Growth rates and ages of the small bamboo coral Acanella arbuscula in the Northwest Atlantic - Laura F. Piccirillo; Evan Edinger; Bárbara de Moura Neves; Meghan Burchell; Graham D. Layne; Vonda E. Hayes (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Late Holocene and recent cold-water coral calcium carbonate production in Guilvinec Canyon, Bay of Biscay, France - Evan Edinger; Jean-François Bourillet; Lenaïck Menot; Franck Lartaud; Mathilde Chemel; Stephan Jorry (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Associations between iKaluk/Arctic charr (Salvelinus alpinus) and estuarine benthic diatom habitats in nearshore Nunatsiavut waters - Zachary MacMillan-Kenny; Mary Denniston; Evan Edinger; Adam Templeton; David Côté; Audrey Limoges; Katleen Robert (Polar Biology, 2025)
iKaluk, Inuttitut for Arctic charr ( Salvelinus alpinus ), holds significant commercial and cultural value for Inuit communities throughout Nunatsiavut. Studies evaluating iKaluk habitat associations in freshwater are plentiful; however, there is limited information on the ecological makeup and sediment characteristics of anadromous charr habitats in marine environments. This study investigated the benthic associations of Arctic charr during their marine residency period in Nain, Nunatsiavut, using underwater videos, harvester-identified fishing locations, and acoustic telemetry. Drop-camera surveys were deployed on previously placed hydrophone acoustic receivers and within harvester-identified fishing locations to describe and quantify available benthic habitats in the study area. Telemetry information was used to identify charr occupancy hotspots, and calculate habitat suitability indices. A total of 248,056 benthic organisms belonging to 63 morphotaxa were identified within the 125 video drops used for benthic community characterization and these represented five faunal assemblages. Marine phase charr occupied estuaries to a greater degree than other fjord or coastal headland environments and these habitats were typically characterized by fine sediments covered by high densities of brittle stars (Ophiuroidea spp.) and benthic diatom mats. The consistent presence of diatomaceous sediments is indicative of abundant foraging opportunities. The importance of these habitats to iKaluk, need to be considered in future marine planning given the cultural and ecological value of this species to many northern communities that face growing threats from environmental change.

Local size structure and distribution of demersal fish in relation to sea pens and other benthic habitats in a deep-sea soft-bottom environment - Marion Boulard; Krista Baker; Peter Lawton; Evan Edinger (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

Incorporating functional traits with habitat maps: patterns of diversity in coastal benthic assemblages - Shreya Nemani; Benjamin Misiuk; David Cote; Evan Edinger; Julia Mackin-McLaughlin; Adam Templeton; Katleen Robert (Frontiers in Marine Science, 2024)
Benthic species assemblages are groups of species that co-occur on the seafloor. Linking assemblages to physical environmental features allows for understanding and predicting their spatial distribution. Species identity and abundance are commonly quantified using a taxonomic approach to assess benthic diversity, yet functional traits that describe the behavior, life history, and morphology of a species may be equally or more important. Here, we investigate the biodiversity of five benthic species assemblages in relation to their habitat and environmental conditions in an Ecologically and Biologically Significant Area (EBSA) along Canada’s east coast, using both a taxonomic approach and biological traits analysis. Random Forest regression was applied to map spatial patterns of functional and taxonomic diversity metrics, including richness, Shannon index, and Rao’s quadratic entropy. We evaluate discrepancies between related taxonomic and trait measures, and the community-weighted mean of trait data was calculated to characterize each assemblage. Taxonomic and functional richness – representing the number of species and the species community volume in the trait space, respectively – showed similar spatial patterns. However, when considering diversity, which also accounts for the relative abundance and differences among species or traits, these patterns diverged. Taxonomically different assemblages exhibited similar trait compositions for two assemblages, indicating potential trait equivalencies, while one assemblage exhibited traits potentially indicating sensitivity to human activity. The taxonomic and functional metrics of richness and diversity were low close to the coast, which could be indicative of disturbance. Consideration of functional metrics can support spatial planning and prioritization for management and conservation efforts by assessing the sensitivity of traits to different stressors.

The effect of small-scale habitat features on groundfish density in deep-sea soft-bottom ecosystems - Marion Boulard; Peter Lawton; Krista Baker; Evan Edinger (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Benthic megafaunal biodiversity of the Charlie-Gibbs fracture zone: spatial variation, potential drivers, and conservation status - Poppy Keogh; Rylan J. Command; Evan Edinger; Aggeliki Georgiopoulou; Katleen Robert (Marine Biodiversity, 2022)
The Charlie-Gibbs Fracture Zone (CGFZ) is a prominent geological feature offsetting the Mid-Atlantic Ridge (MAR), consisting of two parallel fractures, creating a highly variable seafloor bathymetry. It has been defined as the most important latitudinal biodiversity transitional zone on the MAR. Despite this recognition, the faunal communities living on the fracture zone have not been extensively described. A remotely operated vehicle (ROV) was utilised during the TOSCA (Tectonic Ocean Spreading at the Charlie-Gibbs Fracture Zone) survey. The survey included five ROV video transects at depths between 560 and 2900 m. The objectives of the study were to use this video footage to quantify benthic megafaunal density and biodiversity patterns on the CGFZ and their environmental drivers. Species accumulation curves and generalised additive modelling show that depth and the presence of hard substrates play an important role in explaining species richness and abundance at the CGFZ. Coral taxa showed highest abundance between depths of 1500 and 2000 m, while sponge taxa were more abundant between 1750 and 2250 m. A dense sponge aggregation was identified on a ridge feature at 2250 m depth. The high biodiversity and presence of dense sponge aggregations and coral gardens found in this study highlight the need for detailed surveys to help support decisions made by governing bodies on the protection status of the CGFZ.

Sponge communities in the eastern Canadian Arctic: species richness, diversity and density determined using targeted benthic sampling and underwater video analysis - Curtis Dinn; Xinyue Zhang; Evan Edinger; Sally P. Leys (Polar Biology, 2020)

Influence of Deep-Water Corals and Sponge Gardens on Infaunal Community Composition and Ecosystem Functioning in the Eastern Canadian Arctic - Marie Pierrejean; Cindy Grant; Bárbara de Moura Neves; Gwénaëlle Chaillou; Evan Edinger; F. Guillaume Blanchet; Frédéric Maps; Christian Nozais; Philippe Archambault (Frontiers in Marine Science, 2020)

Seafloor mapping to support conservation planning in an ecologically unique fjord in Newfoundland and Labrador, Canada - Beatrice Proudfoot; Rodolphe Devillers; Craig J. Brown; Evan Edinger; Alison Copeland (Journal of Coastal Conservation, 2020)

Enigmatic Deep-Water Mounds on the Orphan Knoll, Labrador Sea - Shawn P. Meredyk; Evan Edinger; David J. W. Piper; Veerle A. I. Huvenne; Shannon Hoy; Alan Ruffman (Frontiers in Marine Science, 2020)

Small-Scale Patterns in the Distribution and Condition of Bamboo Coral, Keratoisis grayi, in Submarine Canyons on the Grand Banks, Newfoundland - Krista D. Baker; Paul V. R. Snelgrove; David A. Fifield; Evan N. Edinger; Vonda E. Wareham; Richard L. Haedrich; Kent D. Gilkinson (Frontiers in Marine Science, 2019)

Investigation of trophic ecology in Newfoundland cold-water deep-sea corals using lipid class and fatty acid analyses - Flora Salvo; Dounia Hamoutene; Vonda E. Wareham Hayes; Evan N. Edinger; Christopher C. Parrish (Coral Reefs, 2018)

Limited Contribution of Small Marine Protected Areas to Regional Biodiversity: The Example of a Small Canadian No-Take MPA - Emilie Novaczek; Victoria Howse; Christina Pretty; Rodolphe Devillers; Evan Edinger; Alison Copeland (Frontiers in Marine Science, 2017)

Deep-water bamboo coral forests in a muddy Arctic environment - Bárbara de Moura Neves; Evan Edinger; Claude Hillaire-Marcel; Esprit Heestand Saucier; Scott C. France; Margaret A. Treble; Vonda E. Wareham (Marine Biodiversity, 2015)

Decadal longevity and slow growth rates in the deep-water sea pen Halipteris finmarchica (Sars, 1851) (Octocorallia: Pennatulacea): implications for vulnerability and recovery from anthropogenic disturbance - Bárbara de Moura Neves; Evan Edinger; Graham D. Layne; Vonda E. Wareham (Hydrobiologia, 2015)

Regional‐scale dominance of non‐framework building corals on Caribbean reefs affects carbonate production and future reef growth - Chris T. Perry; Robert S. Steneck; Gary N. Murphy; Paul S. Kench; Evan N. Edinger; Scott G. Smithers; Peter J. Mumby (Global Change Biology, 2015)
Coral cover on Caribbean reefs has declined rapidly since the early 1980's. Diseases have been a major driver, decimating communities of framework building Acropora and Orbicella coral species, and reportedly leading to the emergence of novel coral assemblages often dominated by domed and plating species of the genera Agaricia , Porites and Siderastrea . These corals were not historically important Caribbean framework builders, and typically have much smaller stature and lower calcification rates, fuelling concerns over reef carbonate production and growth potential. Using data from 75 reefs from across the Caribbean we quantify: (i) the magnitude of non‐framework building coral dominance throughout the region and (ii) the contribution of these corals to contemporary carbonate production. Our data show that live coral cover averages 18.2% across our sites and coral carbonate production 4.1 kg Ca CO 3 m −2 yr −1 . However, non‐framework building coral species dominate and are major carbonate producers at a high proportion of sites; they are more abundant than Acropora and Orbicella at 73% of sites; contribute an average 68% of the carbonate produced; and produce more than half the carbonate at 79% of sites. Coral cover and carbonate production rate are strongly correlated but, as relative abundance of non‐framework building corals increases, average carbonate production rates decline. Consequently, the use of coral cover as a predictor of carbonate budget status, without species level production rate data, needs to be treated with caution. Our findings provide compelling evidence for the Caribbean‐wide dominance of non‐framework building coral taxa, and that these species are now major regional carbonate producers. However, because these species typically have lower calcification rates, continued transitions to states dominated by non‐framework building coral species will further reduce carbonate production rates below ‘predecline’ levels, resulting in shifts towards negative carbonate budget states and reducing reef growth potential.

Erratum to: Petrology and tectonic significance of seamounts within transitional crust east of Orphan Knoll, offshore eastern Canada - Georgia Pe-Piper; Shawn Meredyk; Yuanyuan Zhang; David J. W. Piper; Evan Edinger (Geo-Marine Letters, 2014)

Petrology and tectonic significance of seamounts within transitional crust east of Orphan Knoll, offshore eastern Canada - Georgia Pe-Piper; Shawn Meredyk; Yuanyuan Zhang; David J. W. Piper; Evan Edinger (Geo-Marine Letters, 2013)

Marine habitat mapping in support of Marine Protected Area management in a subarctic fjord: Gilbert Bay, Labrador, Canada - Alison Copeland; Evan Edinger; Rodolphe Devillers; Trevor Bell; Philippe LeBlanc; Joe Wroblewski (Journal of Coastal Conservation, 2013)

Gold Mining and Submarine Tailings Disposal: Review and Case Study - Evan Edinger (Oceanography, 2012)

Distribution and Accumulation of Mercury Derived from Gold Mining in Marine Environment and Its Impact on Residents of Buyat Bay, North Sulawesi, Indonesia - Markus T. Lasut; Yoshiaki Yasuda; Evan N. Edinger; Jane M. Pangemanan (Water, Air, & Soil Pollution, 2010)

Reproductive biology of the deep-sea octocoral Drifa glomerata in the Northwest Atlantic - Zhao Sun; Jean-François Hamel; Evan Edinger; Annie Mercier (Marine Biology, 2010)

Sea level and paleotemperature records from a mid-Holocene reef on the North coast of Java, Indonesia - Karem Azmy; Evan Edinger; Joyce Lundberg; Wilfredo Diegor (International Journal of Earth Sciences, 2010)

Oceanography and reefs of recent and Paleozoic tropical epeiric seas - Evan N. Edinger; St. Paul Copper; Michael J. Risk; Warsito Atmojo (Facies, 2002)